2001
DOI: 10.1096/fj.00-0534fje
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis‐inducing factor regulates hepatic gene expression via the transcription factors NF‐κΒ and STAT3

Abstract: A novel protein, proteolysis-inducing factor (PIF), has been isolated from the urine of patients with pancreatic cancer and is capable of inducing muscle proteolysis in vitro. Only adult skeletal muscle and liver exhibit substantial binding of PIF. We have investigated the effect of PIF on hepatic gene expression. Primary cultures of human hepatocytes and the human cell line HepG2 were incubated in the presence of PIF to assess its effects on hepatic transcription factors, proinflammatory cytokine production, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
78
0
10

Year Published

2003
2003
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 28 publications
1
78
0
10
Order By: Relevance
“…This may be essential to its function as a cachetic factor, as dermcidin expression does not appear sufficient to induce cachexia (Monitto et al, 2004). Similarly, deglycosylated PIF lacks proteolytic activity in murine gastrocnemius muscle (Todorov et al, 1996(Todorov et al, , 1997, and in our experiments it was the fully glycosylated PIF molecule that influenced hepatic cell NF-kB and STAT3 activity and gene expression (Watchorn et al, 2001(Watchorn et al, , 2002. However, the PIF aminoacid sequence lacks typical consensus N-and O-glycosylation sites and the mechanism of glycosylation remains unknown.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…This may be essential to its function as a cachetic factor, as dermcidin expression does not appear sufficient to induce cachexia (Monitto et al, 2004). Similarly, deglycosylated PIF lacks proteolytic activity in murine gastrocnemius muscle (Todorov et al, 1996(Todorov et al, , 1997, and in our experiments it was the fully glycosylated PIF molecule that influenced hepatic cell NF-kB and STAT3 activity and gene expression (Watchorn et al, 2001(Watchorn et al, , 2002. However, the PIF aminoacid sequence lacks typical consensus N-and O-glycosylation sites and the mechanism of glycosylation remains unknown.…”
mentioning
confidence: 74%
“…Screening of tissues for PIF binding demonstrated substantial binding only to skeletal muscle and liver (unpublished observation), and we have investigated the effect of PIF on liver cells. In primary hepatocytes and HepG2 cells, PIF was found to activate the transcription factors NF-kB and STAT3, resulting in the stimulation of IL-8, IL-6 and CRP production, and the inhibition of transferrin production (Watchorn et al, 2001). Proteolysis-inducing factor was also found to induce the expression of NF-kB, IL-6, IL-8, ICAM-1 and VCAM and the shedding of syndecans in the liver endothelial cell line SK-HEP-1 and human umbilical vein endothelial cells, but not in pulmonary artery endothelial cells (Watchorn et al, 2002).…”
mentioning
confidence: 99%
“…Proteolysis-inducing factor has also been shown to activate NFkB in primary hepatocytes and the human cancer cell line HepG2, resulting in the increased production of interleukin-6 and -8 (IL-6 and IL-8) and C-reactive protein and the decreased production of transferrin (Watchorn et al, 2001). There was also an increase in ICAM-1, another NF-kB-inducible gene.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that EPA also affects a downstream pathway involved in induction of proteasome expression by 15(S)-HETE, possibly a nuclear transcription factor, since Ross et al (1999) have shown that in the pancreatic cancer cell line, MiaPaCa 2, exposed to EPA for 2 h prior to a pulse of TNF-a, I-kBa was preserved, suggesting an effect of EPA in stabilising the NF-kB complex in the cytoplasm. Watchorn et al (2001) have shown PIF to activate both the transcription factors NF-kB and STAT3 in hepatic cells. Li et al (1998) showed that TNF-a stimulated protein loss in C 2 C 12 myotubes involved the ubiquitin -proteasome proteolytic pathway and was accompanied by nuclear translocation of NF-kB to its targeted DNA sequence by stimulating phosphorylation, ubiquitin conjugation and proteolysis of I-kBa.…”
Section: Discussionmentioning
confidence: 99%